Investigation results of kinematic and dynamic indicators of tiller with vertical rotation axis in orchards soil cultivation - Sargsyan, S.F. (2020)
The results of experimental-theoretical investigations on the tillers with vertical rotation axis in soil cultivation and weed eradication in orchards are introduced in the article. Upon the developed theory of rotary tiller kinematics and dynamics calculation the following points have been set up. The reliability of the developed calculation theory has been verified through the results of conducted experiments, the difference hasn't exceeded 5%, which is explained by the inhomogeneity of the treated medium and changeability of the straightness of the garden rows.